NOVELTIES IN PANICUM (POACEAE) FROM INDIA - NAIK, V. N.; PATUNKAR, B. W. (REINWARDTIA, 1980)
Four novelties in the genus Panicum L. namely P. phoiniclados,P. deccanense and P. paianum together with its variety minor have been described from materials collected from the Marathwada region of the Deecan plateau.